Rancang Bangun Sistem Informasi Geografis Untuk Pemetaan Lokasi Tempat Ibadah Di Kota Mataram Menggunakan Metode Extreme Programming: Design of Geographic Information System For Mapping The Location of Worship in Mataram City Using Extreme Programming Method - Ricky Satria; Royana Afwani; Sri Endang Anjarwani (Journal of Computer Science and Informatics Engineering (J-Cosine), 2021)
In Mataram city, finding places of worship is quite difficult for foreigners because they do not know the position/road around them. And currently, the data management of places of worship is still carried out using Ms. Excel by the Departemen Agama NTB which makes data collection ineffective and inefficient in searching and updating existing data. In this final project research, the researcher designed and built a Geographic Information System for Mapping the Location of Places of Worship in Mataram City to provide information and layout of places of worship in Mataram City, and can make it easier for the Ministry of Religion to collect data from the system that makes data management of existing places of worship more effective and efficient. This final project research uses the Extreme Programming (XP) system development method because one of the characteristics of XP itself involves the client during the system development process to minimize errors in the system and according to client needs.